Analyzing The Potential Utilization of Discord Application As A Digital Arabic Linguistic Environment - Hatfina Izazi Asy Syahida Imani; Khurun ‘Ainal Haq; Shinta Mardiyatul Fitriyah; Muhammad Lukman Arifianto (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
The purpose of this study was to present a new concept in viewing the Discord application by comparing the concept of the language environment with the use of Discord as a language learning medium. This research used exploratory qualitative research using a grounded theory approach and in-depth studies regarding the concepts and theories needed. Data are collected by direct observation on one of the Arabic learning servers, namely the Learn Arabic server, and questionnaires. The results of the data analysis showed that the activities on the Discord server indicate new possibilities in using the Discord application as a digital Arabic linguistic environment. The practical implication of this research is to raise awareness among educators and Arabic students about the value of the Discord application as a language learning medium.